Climate variation in the Amazonian peneplain due to deforestation and urban expansion in Iquitos - Peru, between 1984 and 2023 - Jimena Yuijan Rodriguez Prieto, Alexia (2024)
Tropical forests suffer the loss of millions of hectares every year due to land use and land cover change for agricultural production, resource exploitation and settlement development, contributing to global warming and altering the environmental conditions of the territory, as in the city of Iquitos in the Peruvian Amazon, where it is necessary to know how these impacts affect its population, activities and ecosystems. The objective of the study was to analyse the effects of urban expansion and global warming on the climate of the city of Iquitos, as well as its variation in relation to the climate of the towns of Pebas and Trompeteros, in the Peruvian Amazonian peneplain in the period 1984-2022, for which meteorological data from the study area was processed, maps of ecosystems and satellite images were processed to determine levels of vegetation vigour by calculating the normalised difference vegetation index in three quadrants over the towns of Iquitos, Pebas and Trompeteros, of similar latitude and altitude, but with different forest conservation status. The results showed that the city of Iquitos has tripled in size since 1984, with an average growth of 58.4 hectares per year, causing a heat island effect, with at least 1.1°C more than nearby rural areas, and a decrease of up to 1,000 millimetres of annual rainfall, with the effect being greater in its area because 33% of its territory has been altered, compared to Pebas and Trompeteros, which have more than 88% of their territories covered by primary forests. It is concluded that population growth drives deforestation for urbanisation, agricultural production and other purposes, which in countries with weak institutions is uncontrolled and unregulated. Likewise, deforestation increases the effect of global warming on the local climate due to the loss of environmental services provided by forests, such as temperature regulation and moisture supply, affecting the vigour of local vegetation.